Pengaruh Biaya Produksi terhadap Penjualan Ikan Nila pada Balai Benih Ikan Lokal (BBIL) Di Desa Cukan Lipai Kecamatan Batang Alai Selatan Kabupaten Hulu Sungai Tengah - Purna Kusumayana; Yudhi Harianto; Andi Suci Anita (Rawa Sains: Jurnal Sains STIPER Amuntai, 2015)
This study aims to determine the extent to which production costs have an effect on the sale of tilapia at the Fish Seed Center of Cukan Lipai Village, Batang Alai Selatan District, Hulu Sungai Tengah Regency. The results showed that the production cost had an effect on the selling price of 64.1% in tilapia hatchery business in the Cukan Lipai Village, Batang Alai Selatan District, Hulu Sungai Tengah Regency. While the remaining 35.9% can be influenced by other variables besides production costs